GUERILLA MARKETING: TAKTIK PERPUSTAKAAN UNTUK EKSIS DALAM MENGHADAPI GENERASI MILENIAL - Resty Jayanti Fakhlina (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
The big challenge facing the library to be known by the millennial generation is the rapid development of information and communication technology. This rapid development makes the millennial generation very easy to obtain information, regardless of the information are fact or hoaxes. This makes the millennial generation lazy to use library facilities because they think, all the information they need can be obtained through the internet. However, using the internet without knowledge can lead to false information. Therefore, they must utilize the services provided by the library to obtain information that is correct and in accordance with their needs. In order for the millennial generation to know about the existence of libraries, special marketing tactics like Guerilla Marketing are needed to attract their interest in utilizing library services.